Securing campus access control and management system with attribute-based access control (ABAC) - Chong, Chee Xuan (2022)
Campus Access Control and Management System of UMS Campus still relies on conventional manual registration and spreadsheet management, resulted in a time-consumed registration process, inconsistent data entries, and disclosure of visitor’s privacy. The registration and access control becoming worst during the covid-19 pandemic. Malaysia’s universities are using various systems and platforms to manage their campus access control. For example, the M-Pass ID system from Monash University, Smart Card system from Universiti Sains Malaysia and so more. However, the access control of these systems primarily constructed based on a conventional role-based access control policy that authenticated with a password, which subjected to password guessing attacks and granted permission is based on the user’s role, not on data operations and objects. To address these gaps, this project aimed to propose a Campus Access Control and Management System with Attribute-Based Access Control (ABAC) which granted access to the user by attributes. The project aims to investigate lightweight Attribute-based Access Control from the perspective of computation speed of setup, verify and granting process by using systematic literature review and experimental approach, design and develop a web-based management system with attribute-based encryption on access control by using the waterfall approach, and evaluate the usability performance of the developed campus access control and management system by using System Usability Scale (SUS) approach. A large number of literature reviews from a different angle are expected, interviewing the security division also done for further analysis. Then the experiment on attribute-based encryption was undergoing and chose the best to implement into the project. The expected outcome of this project is a web-based campus access control and management system that eases the UMS security division in registering managing visitor entries.